On Not Being Lost in Translation: Creative Strategies to Approach Multiculturalism in Esperanto - Burghelea, Manuela (Język. Komunikacja. Informacja, 2019)
This article examines translation practices into Esperanto, a constructed language with 130 years of existence and which is meant to serve neutral international communication. As such, one of Esperanto’s practical applications is to render works from around the world and from different times accessible to a worldwide community of speakers. We analyse the role played by translation in the development of Esperanto and in the creation of an Esperanto community. We argue that translation into Esperanto possesses a key social function and conveys values that go beyond the mere transfer of semantics. In doing so, we apply an interdisciplinary perspective and draw on approaches from translation studies, linguistics, anthropology and intercultural communication studies. Placing these approaches within a dialogue is beneficial for a deeper understanding of the various strategies employed by Esperanto translators in order to accommodate and to inform the Esperanto cultural horizon.